Government Ecology and the Indigenous Religion of the Suku Anak Dalam: Intersubjective Relations in Forest Conservation in Jambi, Indonesia - Khairun Najib (Institut Pertanian Bogor (IPB University), 2020)
Integrating customary-religious values of an indigenous tribe